2000
DOI: 10.1530/eje.0.1430085
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-binding globulin as a marker for hyperinsulinemia and/or insulin resistance in obese children

Abstract: Objective: A relationship between hyperinsulinemia and decreased serum sex hormone-binding globulin (SHBG) has been described in adults. We evaluated the usefulness of SHBG as an index of hyperinsulinemia and/or insulin resistance in obese children (aged 6±9 years) of both sexes and its possible in¯uence on the androgenic status. Design: We carried out a cross-sectional study of cases and controls. We studied 61 obese children (22 males, 39 females) with body mass index (BMI) superior to the 90 th percentile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
6
27
0
4
Order By: Relevance
“…Sex hormone-binding protein has the effect of controlling the action of testosterone, and acts as an amplifier of estrogenic action. There are several reports of a negative correlation between serum SHBG and insulin levels [21][22][23]. In view of these facts, we examined in this study, rat sex-related hormone dynamics and SHBG in OLETF rats which were used as a human type 2 diabetes model.…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormone-binding protein has the effect of controlling the action of testosterone, and acts as an amplifier of estrogenic action. There are several reports of a negative correlation between serum SHBG and insulin levels [21][22][23]. In view of these facts, we examined in this study, rat sex-related hormone dynamics and SHBG in OLETF rats which were used as a human type 2 diabetes model.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, SHBG is thought to bind and transport sex steroids and thereby to regulate their biological actions and signaling to target tissues (2). Recently, many epidemiological studies have shown that low serum SHBG levels are associated with insulin resistance and hyperinsulinemia (3,4), and to increase serum SHBG as well as insulin sensitivity (7,8). Metformin treatment for patients with insulin resistance often results in an increase in serum SHBG (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these calculation models, which allow easier and faster assessment, some investigators have advocated the use of sex hormone-binding globulin (SHBG) as a predictive marker of IR in women with hyperandrogenic syndrome (14). However, some groups have only described very small populations of women with PCOS (15,16), or used the Rotterdam criteria to define PCOS (17), while other authors have described the phenomenon additionally in postmenopausal women (18) or in obese children without changes in their androgenic status (19). Recently, cutoff points for insulin sensitivity indices for the simple identification of insulin-resistant patients have been defined (20).…”
Section: Introductionmentioning
confidence: 99%